2022
DOI: 10.1038/s41598-022-06192-w
|View full text |Cite
|
Sign up to set email alerts
|

Tissue miR-200c-3p and circulating miR-1290 as potential prognostic biomarkers for colorectal cancer

Abstract: Epithelial–mesenchymal transition (EMT)-related cancers generally elicit low immune responses. EMT is regulated by several microRNAs (miRNAs) in cancers. Thus, this study aimed to evaluate the prognostic potential of EMT-related miRNAs as biomarkers in colorectal cancer (CRC). Formalin-fixed paraffin-embedded tumor and normal tissue and plasma samples were obtained from 65 patients with pathologically confirmed CRC. In addition, plasma samples were obtained from 30 healthy volunteers. Immunohistochemical stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Additionally, extracellular vesicles from other biological matrices, such as supernatants of malignant ascites, had higher levels of miR-200c-3p than benign peritoneal fluid [ 35 ]. Both tumor-suppressive and tumor-promoting roles have been described for miR-200c-3p; this molecule suppresses EMT, migration, invasion, and drug resistance [ 36 ], and it promotes drug resistance and reduces T-cell infiltration [ 37 , 38 ]. Similarly, to our work, exposure of ovarian cancer spheroids and gastric cancer cells to miR-200c-3p and miR-200c-3p-rich supernatants of malignant ascites, respectively, increased cell migration [ 35 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, extracellular vesicles from other biological matrices, such as supernatants of malignant ascites, had higher levels of miR-200c-3p than benign peritoneal fluid [ 35 ]. Both tumor-suppressive and tumor-promoting roles have been described for miR-200c-3p; this molecule suppresses EMT, migration, invasion, and drug resistance [ 36 ], and it promotes drug resistance and reduces T-cell infiltration [ 37 , 38 ]. Similarly, to our work, exposure of ovarian cancer spheroids and gastric cancer cells to miR-200c-3p and miR-200c-3p-rich supernatants of malignant ascites, respectively, increased cell migration [ 35 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial aim of the study was to comprehensively characterize the miR-200 family as a potentially pivotal coordinator between EMT and immune evasion in BTC. This seemed intriguing, because [1] miR-200 family expression and EMT status are tightly connected [ 24 , 25 ]; [2] members of the miR-200 family have already been mentioned to influence the expression of several ICs [ 26 ]; [3] it has been reported that EMT status of cancer cells predicts the response of patients to IC blockade [ 16 ]; and [4] miR-200c-3p expression was identified as prognostic biomarker for colorectal cancer, suggesting a key role for this miRNA in regulating the EMT-immune crosstalk [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a negative relationship between the levels of miR-22 and miR-24 and plasma PD-1 levels in patients who responded well to treatment for an extended period suggests that a network of miRNAs may play a role in suppressing the expression of immune checkpoints, primarily through the involvement of the miR-20 family (p < 0.05) [ 88 ]. The levels of miR-1290 in circulating plasma exhibited an inverse correlation with the presence of CD3-negative, CD8-negative, and PD-1-positive cells [ 89 , 90 ]. In a group of melanoma biopsies that had not been treated with PD-1 inhibitors, it was observed that higher levels of miR-100-5p (p-value = 0.036) and miR-125b-5p (p-value = 0.025) expression were linked to better results when treated with anti-PD-1 immunotherapy [ 91 ].…”
Section: Micrornas: Bridging the Gap Between Gene Regulation Immune C...mentioning
confidence: 99%
“…There was an inverse correlation observed between miR-200c-3p and the expression of immune cell markers, including CD3, CD4, and CD8. Additionally, miR-200c-3p displayed a negative correlation with the presence of PD-L1, an immune marker [ 89 , 101 ]. In the initial stage of clinical trials, the utilization of MRX34 , a newly developed synthetic version of miR-34a-5p , has demonstrated a notable reduction in the expression of PD-L1 in tumors.…”
Section: Micrornas: Bridging the Gap Between Gene Regulation Immune C...mentioning
confidence: 99%